Design and implementation of an automatic irrigation system for plants in Lima-Perú - Astuhuaman-Medina, Jean Piere; Granados-Zárate, Adrian Humberto; Marcatinco-Gonzales, Jhonel Wilfredo; Segura-Viteri, Martin Fernando; Morante-Medina, Aldhair; Castro-Vargas, Cristian (Institute of Advanced Engineering and Science, 2025)
In many regions of the world, water used in agriculture becomes a scarce and costly resource over time. It is necessary to make efficient use of this vital resource. For this reason, we opted for an innovative project that can be of great use for agriculture, incorporating information and communication technologies such as the internet of things (IoT), databases, and smartphone applications. The research proposes an IoT system to control and monitor crops in a specific area based on the ESP32 microcontroller, using the DHT11 sensor to collect temperature and relative humidity data. The sensors send the information to the central node for the wireless communication part. The central node activates the actuators to control and store the information in a database for corresponding monitoring. The mobile application displays the results from the database and causes them to be turned on and off manually. The system was implemented for home plant cultivation but can be used for other types of cultivation due to its flexibility.